2012
DOI: 10.1021/bi3010945
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanistic Studies of the Spore Photoproduct Lyase via a Single Cysteine Mutation

Abstract: 5-thyminyl-5,6-dihydrothymine (also called spore photoproduct or SP) is the exclusive DNA photo-damage product in bacterial endospores. It is repaired by a radical SAM (S-adenosylmethionine) enzyme, the spore photoproduct lyase (SPL), at the bacterial early germination phase. Our previous studies proved that SPL utilizes the 5′-dA• generated by SAM cleavage reaction to abstract the H6proR atom to initiate the SP repair process. The resulting thymine allylic radical was suggested to take an H atom from an unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(80 citation statements)
references
References 102 publications
(258 reference statements)
6
73
1
Order By: Relevance
“…IPP and GPP were purchased from Isoprenoids. [4][5][6][7][8][9][10][11][12][13][14] C]IPP was purchased from PerkinElmer Life Sciences. HEK293T cell line was obtained from ATCC.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…IPP and GPP were purchased from Isoprenoids. [4][5][6][7][8][9][10][11][12][13][14] C]IPP was purchased from PerkinElmer Life Sciences. HEK293T cell line was obtained from ATCC.…”
Section: Methodsmentioning
confidence: 99%
“…For example, radical SAM-dependent enzymes participate in the biosynthesis of herbicides, antibiotics, vitamins, co-factors such as biotin and thiamin, and various other natural products (2,(5)(6)(7)(8). They also function in the modification of ribosomal and transfer RNAs (9,10) and DNA repair (11) and in the post-translational modification of peptides and proteins (12)(13)(14). Sequence analyses indicate that there are potentially thousands of members of the radical SAM superfamily, but to date, relatively few of these enzymes have been isolated and characterized (15,16).…”
Section: Radical S-adenosyl-l-methionine-dependent (Sam)mentioning
confidence: 99%
See 1 more Smart Citation
“…6 The SPL catalyzes the direct repair of the SP-lesion, utilizing a radical mediated mechanism (Fig. 1A) 13 showed that the allyl reducing moiety is a conserved cysteine. A recent crystal structure of the SPL from Geobacillus thermodenitrificans 14 in complex with the lesion 15 ( Fig.…”
mentioning
confidence: 99%
“…However, other studies using smaller but chemically better-defined substrates have found much lower turnover numbers (72,(75)(76)(77)80). Most other in vitro SPL studies utilized dinucleotide or dinucleoside SP as substrate and found that the ratio between 5Ј-dA generated and SP repaired ranges between 1 and 2, suggesting that SAM is partially regenerated.…”
Section: Spl Mechanism: the Controversialmentioning
confidence: 99%